Freedom and Capitalism in Early Modern Europe - Rössner, Philipp Robinson. author. aut Link
XIII, 175 p. 4 illus.
Keywords: This book hinges upon ideas and discourses variously known under labels such as “Mercantilism” and “Cameralism”. Often viewed as antithesis of capitalism, inclusive institutions and good economy in the “West”, this book re-assembles them and builds them into a coherent origin story of modern capitalism. It explores the field of intellectual and conceptual history, especially the history of Renaissance and Mercantilism in a longer history of capitalism. Rather than hindrances, the author argues that Mercantilist and Cameralist political economies presented essential stepping stones of modern capitalism, in Britain and beyond. This book will be of interest to academics and students in general economic history, the history of capitalism, economic development and the history of economic thought.